Modified decomposition method for nonlinear Volterra-Fredholm integral equations - Bildik, Necdet; İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2007)
In this paper, the nonlinear Volterra-Fredholm integral equations are solved by using the modified decomposition method (MDM). The approximate solution of this equation is calculated in the form of a series with easily computable components. The accuracy of the proposed numerical scheme is examined by comparison with other analytical and numerical results. Two test problems are presented to illustrate the reliability and the performance of the modified decomposition method. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Construction